OUTCOME OF TWO COLUMN ACETABULAR FRACTURES TREATED OPERATIVELY THROUGH SINGLE POSTERIOR APPROACH - Razaq, Muhammad Naeem ur; Khan, Muhammad Ayaz; Ali, Abbas (Journal of Ayub Medical College Abbottabad, 2016)
Background: Involvement of both columns in acetabular fractures is a common presentation, these fractures create a challenging situation for the surgeons in terms of understanding the dimensions of osseous injury and selection of surgical approach. The study was done with an objective to evaluate the efficacy of single posterior approach for acetabular fractures involving both columns directly reducing the posterior wall and column and indirectly reducing the anterior column. Method: An evaluation of 25 adult patients 18 male and 7 female presenting in the accident and emergency department of Khyber Teaching Hospital from December 2013 to June 2015 having acetabular fracture involving both the anterior and posterior column were included in this case series study. All patients were operated within 8 days of injury by a single operating team. Exposing and reducing the posterior acetabular column through kockerlengenbeck approach did open reduction and internal fixation with reconstruction plate and cortical screws. Additional lag screw was used to stabilize anterior column after indirect reduction with confirmation through C- arm and digital palpation through the greater sciatic notch. Patients were followed up for 6 months and Harris Hip score was evaluated after the end of the follow up period and the result was analysed. Result: Majority of the patients 20 out of 25 had haris hip score more than 90 after 6 months of the operative management. Conclusion: It is suggested that acetabular that fractures involving both the acetabular columns in certain situations, may be managed by a single posterior approach as it is associated with good clinical outcome and involves lesser soft tissue complications. Keywords: Acetabular fracture; Management; Outcome; Two column acetabular fracture; Posterior approach